Research on construction of professional strength development exercises for women athletes Rowing National youth team at Da Nang National Sports training center - Hung, N. X.; van Diep, T. (International Journal of Physical Education, Fitness and Sports, 2020)
The use of traditional research methods has evaluated theProfessional strengthof woman female rowing boat racing young nation team at National Sports Training Center Da Nang as a basis for selection, Appropriate exercise to develop endurance for a female athlete rowing boat racing young nation team at National Sports Training Center Da Nang, olong with a science-based program that is tailored to the actual conditions of theboat racing training program atthe National Sports Training Center Da Nang (Vietnam).